Small States in Global Governance: Campaign Strategies for Non-Permanent UN Security Council Membership - Mammadova, Rufina; Eminova, Nazrin; Gabilova, Gulshan (My University, 2026)
This paper explores how small states win the United Nations Security Council non- permanent membership elections through strategic campaigns, building coalitions and issue- based positioning. The literature review of the paper critically evaluates existing literature about UNSC elections. Fragmentation and the need for differentiation of types of strategies and norm alignment are exposed and highlighted in this section. The paper utilizes neoliberal institutionalism and small state theories to explain the success of small states to prove their influence by focusing on multilateral engagement, soft power, and diplomatic networks. Employing qualitative documentary analysis, the methodology section provides a structured comparative case study. The compared cases of Estonia, Jordan, Costa Rica, and Kazakhstan shows that long-term preparation, regional coalitions, and niche policy priorities significantly contribute to electoral success. Policy alternatives evaluate strategic pathways and offer three policy alternatives to Azerbaijan for future non-permanent seat on the United Nations Security Council (UNSC), employing comparative analysis of Estonia, Jordan and Costa Rica. The paper finds that Estonia, Jordan, and Costa Rica secured UNSC seats throughout diverse strategies, including long-term preparation, regional coalition-building, and norm- based positioning. Based on these cases, it suggests that Azerbaijan build early diplomatic involvement, widen cross-regional coalition, and shape its priorities as provision to international peace and security.